Bibliometric and meta-analysis on the publication status, research trends and impact inducing factors of JA–SA interactions in plants - Long Jiao; Rongrong Tan; Xun Chen; Hongjuan Wang; Danjuan Huang; Yingxin Mao (Frontiers in Plant Science)
Interactions between jasmonic acid (JA) and salicylic acid (SA) pathways in plants are important for regulating metabolite production and resistance functions against environmental stresses. These interactions in plants have mostly been reported to be antagonistic, but also to be synergistic under specific external inducing conditions. At present, publications on plant JA–SA interactions lack a bibliometric analysis. External inducing factors that elicit synergism of JA–SA interactions need to be explored. Here, we use bibliometrics to analyze publications on plant JA–SA interactions over the past three decades, and analyze external inducing factors that influence the quality of JA–SA interactions in plants by meta-analysis. More contributions have been made by authors in China, Netherlands, the United States of America, and Germany than elsewhere. Considerable research has been performed on variation in plant defense mediated by two pathways, the transduction mechanisms of JA–SA signaling crosstalk, and plant hormone signaling networks. Meta-analysis showed that the excitation sequence of the two pathways, and the concentrations of pathway excitors are key factors that affect pathways interactions. The JA and SA pathways tend to be reciprocally antagonistic when elicited simultaneously, whereas JA–SA interactions tend to be synergistic when the two pathways are elicited at different times and the pre-treated inducer is at a lower concentration. The SA pathway is more susceptible to being synergized by the JA pathway. Key molecular nodes identified in the JA–SA signaling interaction in model plants, and prospects for future research are discussed.